ANALISIS USAHA KERAJINAN SABUT KELAPA DI KABUPATEN KULON PROGO DAERAH ISTIMEWA YOGYAKARTA - dheny arina hartawaty; Handayani Indah Susanti (Agroland: Jurnal Ilmu-ilmu Pertanian, 2020)
Agricultural sector plays important role in the national economy. In Kulon Progo regency, one of commodities in agricultural sector is coconut tree. One of its products is broom made from its coir in Sendangsari village Pengasih Kulon Progo. The objective of this research was to analyze cost, profit, revenue, profitability, risk, and efficiency from coir craft business in Kulon Progo. It used descriptive method. The research was conducted in Pengasih subdistrict Kulon Progo regency, exactly in Klegen subvillage of Sendangsari village. Primary data was obtained through direct interview with 30 coir broom producer using structured questionnaire and other data supporting the research objective. Secondary data was obtained from institutions such as Kulon Progo Statistic Bureau and other related source. The broom handicraft business was profitable and feasible to be developed, R/C ratio was 2.05 indicating that the revenue generated by the business was IDR 205,000. The profit earned by the broom craft business was IDR 105.00. The business risk and the lower limit of the profit was IDR 1,553,613.50 with deviation standard of 398,942.63; coefficient of variation of 0.26; and the lower limit of profit was IDR 755,728.24. Keywords: Coconut Coir Craft and business efficiency.